PENGARUH KUALITAS KEHIDUPAN KERJA (QUALITY OFWORKLIFE) DAN KETIDAKAMANAN KERJA (JOB INSECURITY) TERHADAP NIAT KARYAWAN UNTUK MENINGGALKAN PEKERJAAAN (TURNOVER INTENTION) DENGAN MEDIASI KOMITMEN ORGANISASIONAL (ORGANIZATIONAL COMMITMENT) - Zaenuri, Ahmad; Eric Santosa, Markus S urkamta (Jurnal Ilmiah Telaah Manajemen, 2017)
This study to determine the effect of the quality of work life and job insecurity on turnover intention with the mediation of organizational commitment. This research was conducted contract employee in Semarang PT.AST with the number of respondents as many as 293 people. The research instrument used a questionnaire that tested the validity and reliability, and to explain the influence of independent variables on the dependent variable using a multiple linear regression equation, whereas hypothesis testing using F-test, t test and the beta coefficient. The sampling technique in this research is proporsionl stratified random sampling. The results showed that the quality of work life positive and significant effect on organizational commitment, job insecurity does not affect the organizational commitment, the quality of work life does not affect the turnover intention, job insecurity positive and significant effect on the turnover intention, organizational commitment does not affect the turnover intention, organizational commitment does not mediated the effect of the quality of work life and job insecurity with turnover intention. Keywords: Quality of work life, job insecurity, organizational commitment, turnover intention